RANCANG BANGUN SISTEM INFORMASI MANAJEMEN PROYEK BERBASIS WEB PADA PT SEATECH INFOSYS - Doni Darmawan; Anita Ratnasari (ISB Atma Luhur, 2020)
Every company engaged in IT Consulting is in need of an application that can help management control the projects they work on. This study examines the problems that occur when a company works on a project, aimed at analyzing the effectiveness of the application of project management applications in order to assist the company in presenting information about the project being undertaken or information officers and clients. The study used case studies at PT. Seatech Infosys Considering systems that still use simple data processing tools such as Microsoft Excel, ranging from data logging, data storage to report generation. Thus, it is possible to have errors in recording and less accurate reports are made. The development of the system with the method used is waterfall method. The result of this analysis is to declare that this application is one solution to overcome existing problems, to achieve an effective and efficient activities in supporting the project activities.